Transcranial magnetic stimulation. Which part of the current waveform causes the stimulation? - Corthout, E; Barker, A; Cowey, A (2001)
To investigate the mechanism of transcranial magnetic stimulation (TMS), we compared the directional effects of two stimulators (Magstim 200 and Magstim Super Rapid). First, stimulating visual cortex and facial nerve with occipital mid-line TMS, we found that, for a particular coil orientation, these two stimulators affected a particular neural structure in opposite hemispheres and that, to affect a particular neural structure in a particular hemisphere, these two stimulators required opposite coil orientations. Second, stimulating a membrane-simulating circuit, we found that, for a particular coil orientation, these two stimulators resulted in a peak induced current of the same polarity but in a peak induced charge accumulation of opposite polarity. We suggest that the critical parameter in TMS is the amplitude of the induced charge accumulation rather than the amplitude of the induced current. Accordingly, TMS would be elicited just before the end of the first (Magstim 200) and second (Magstim Super Rapid) phase of the induced current rather than just after the start of the first phase of the induced current.